Multicenter Assessment of Antibiotic Prophylaxis Spectrum on Surgical Infections in Head and Neck Cancer Microvascular Reconstruction. (7th March 2018) - Veve, Michael P.; Greene, Joshua B.; Williams, Amy M.; Davis, Susan L.; Lu, Nina; Shnayder, Yelizaveta; Li, David X.; Noureldine, Salem I.; Richmon, Jeremy D.; Lin, Lawrence O.; Hanasono, Matthew M.; Pipkorn, Patrik; et al.
Abstract : Objective: To characterize and identify risk factors for 30‐day surgical site infections (SSIs) in patients with head and neck cancer who underwent microvascular reconstruction. Study Design: Cross‐sectional study with nested case‐control design. Setting: Nine American tertiary care centers. Subjects and Methods: Hospitalized patients were included if they underwent head and neck cancer microvascular reconstruction from January 2003 to March 2016. Cases were defined as patients who developed 30‐day SSI; controls were patients without SSI at 30 days. Postoperative antibiotic prophylaxis (POABP) regimens were categorized by Gram‐negative (GN) spectrum: no GN coverage, enteric GN coverage, and enteric with antipseudomonal GN coverage. All POABP regimens retained activity against anaerobes and Gram‐positive bacteria. Thirty‐day prevalence of and risk factors for SSI were evaluated. Results: A total of 1307 patients were included. Thirty‐day SSI occurred in 189 (15%) patients; median time to SSI was 11.5 days (interquartile range, 7‐17). Organisms were isolated in 59% of SSI; methicillin‐resistant Staphylococcus aureus (6%) and Pseudomonas aeruginosa (9%) were uncommon. A total of 1003 (77%) patients had POABP data: no GN (17%), enteric GN (52%), and antipseudomonal GN (31%). Variables independently associated with 30‐day SSI were as follows: female sex (adjusted odds ratio [aOR], 1.6; 95% CI, 1.1‐2.2), no GN POABP (aOR, 2.2; 95% CI, 1.5‐3.3), and surgical duration ≥11.8 hours (aOR, 1.9; 95% CI, 1.3‐2.7). Longer POABP durations (≥6 days) or antipseudomonal POABP had no association with SSI. Conclusions: POABP without GN coverage was significantly associated with SSI and should be avoided. Antipseudomonal POABP or longer prophylaxis durations (≥6 days) were not protective against SSI. Antimicrobial stewardship interventions should be made to limit unnecessary antibiotic exposures, prevent the emergence of resistant organisms, and improve patient outcomes.